Epilepsy in Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Epilepsy occurred in 27% (14/52) of children with autism under 10 years of age in a population-basedstudy in the Dept of Child and Adolescent Psychiatry and Pediatrics, University of Goteborg, Sweden.